Ventrolateral medullary functional connectivity and the respiratory and central chemoreceptor-evoked modulation of retrotrapezoid-parafacial neurons - Ott, Mackenzie M. (American Physiological Society, 2011)
The medullary ventral respiratory column (VRC) of neurons is essential for respiratory motor pattern generation; however, the functional connections among these cells are not well understood. A rostral extension of the VRC, including the retrotrapezoid nucleus/parafacial region (RTN-pF), contains neurons responsive to local perturbations of CO(2)/pH. We addressed the hypothesis that both local RTN-pF interactions and functional connections from more caudal VRC compartments—extending from the Bötzinger and pre-Bötzinger complexes to the ventral respiratory group (Böt-VRG)—influence the respiratory modulation of RTN-pF neurons and their responses to central chemoreceptor and baroreflex activation. Spike trains from 294 RTN-pF and 490 Böt-VRG neurons were monitored with multielectrode arrays along with phrenic nerve activity in 14 decerebrate, vagotomized cats. Overall, 214 RTN-pF and 398 Böt-VRG neurons were respiratory modulated; 124 and 95, respectively, were cardiac modulated. Subsets of these neurons were tested with sequential, selective, transient stimulation of central chemoreceptors and arterial baroreceptors; each cell's response was evaluated and categorized according to the change in firing rate (if any) following the stimulus. Cross-correlation analysis was applied to 2,884 RTN-pF↔RTN-pF and 8,490 Böt-VRG↔RTN-pF neuron pairs. In total, 174 RTN-pF neurons (59.5%) had significant features in short-time scale correlations with other RTN-pF neurons. Of these, 49 neurons triggered cross-correlograms with offset peaks or troughs (n = 99) indicative of paucisynaptic excitation or inhibition of the target. Forty-nine Böt-VRG neurons (10.0%) were triggers in 74 Böt-VRG→RTN-pF correlograms with offset features, suggesting that Böt-VRG trigger neurons influence RTN-pF target neurons. The results support the hypothesis that local RTN-pF neuron interactions and inputs from Böt-VRG neurons jointly contribute to respiratory modulation of RTN-pF neuronal discharge patterns and promotion or limitation of their responses to central chemoreceptor and baroreceptor stimulation.